2003
DOI: 10.1140/epjb/e2003-00256-6
|View full text |Cite
|
Sign up to set email alerts
|

Hund?s rule magnetism in C $\mathsf{_{60}}$ ions?

Abstract: We investigate the occurrence of Hund's rule magnetism in C n± 60 molecular ions, by computing the ground-state spin for all charge states n from −3 to +5. The two competing interactions, electronvibration (e-v, including Jahn Teller, favoring low spin) and electron-electron (e-e, including Hund-rule exchange, favoring high spin), are accounted for based on previously computed ab-initio coupling parameters. Treating the ion coordinates as classical, we first calculate and classify the static Jahn-Teller distor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 57 publications
1
25
0
Order By: Relevance
“…Fullerene systems are known to have sizable strengths for both interactions, although the JT interaction is more dominant for alkali-doped region. A recent density functional calculation study 26 has suggested that the fullerene in the hole-doped region may have stronger Hund's rule interaction, with possible applications to cation-doped fullerenes 27 . Finally, we make an observation of an interesting property of the local interaction Eq.…”
Section: Pairing Instability: Dmft Resultsmentioning
confidence: 99%
“…Fullerene systems are known to have sizable strengths for both interactions, although the JT interaction is more dominant for alkali-doped region. A recent density functional calculation study 26 has suggested that the fullerene in the hole-doped region may have stronger Hund's rule interaction, with possible applications to cation-doped fullerenes 27 . Finally, we make an observation of an interesting property of the local interaction Eq.…”
Section: Pairing Instability: Dmft Resultsmentioning
confidence: 99%
“…Also, the spectrum (Fig. 9b) is less dense: the 10 tunneling states (A + H + G) converge to zero energy at strong coupling; the 20 1-phonon tangential states converging to ω (1) τ are fairly well visible; the tangential ω (2) τ , radial ω, and overtone 2 ω A fairly general feature of the vibronic spectrum, especially visible in Figs. 2b, 9b, and 10b, is the rapid drop of several vibronic energies, then followed by a successive climb back at strong coupling where tunneling is suppressed and the motion gradually collapses to oscillations around the adiabatic wells.…”
Section: B the H ⊗ H Jtmentioning
confidence: 95%
“…The HamiltonianĤ depends now on two parameters. Each vibronic eigenvalue traces a 2-dimensional surface as g and α (or equivalently g (1) H and g fixed α, plus circular cuts at fixed g. Like for the G mode, the strong-coupling asymptotic vibronic energies, are determined by the normal frequencies of oscillation around the adiabatic JT minima, and these frequencies now depend on α. The five normal modes separate into a radial vibration of unchanged frequency ω and symmetry A 1 , plus two softer doublydegenerate (of E 1 and E 2 symmetry for D 5 wells and both of E symmetry for D 3 wells) tangential modes, represented in Fig.…”
Section: B the H ⊗ H Jtmentioning
confidence: 99%
See 1 more Smart Citation
“…The JT interaction is stronger than the on-ball exchange coupling [9,17], leading to low-spin ground states and to the stabilization of even-charge anionic states [18,19]. In compounds of even stoichiometry (x = 2, 4) charge fluctuations are hindered both by correlation and JT effects [20][21][22], resulting in insulating and diamagnetic ground states [23][24][25], while in odd stoichiometries of cubic symmetry metallic behaviour and even phonon-mediated superconductivity (for x = 3) are observed [26][27][28].…”
Section: Introductionmentioning
confidence: 99%